Perspectives and Limitations of Neuromarketing Research Methods - A. Yu. Nedelko (Управленческие науки)
In the modern world consumers are overwhelmed with advertising messages and competition among advertisers is becoming harder. That is why there is a need to develop effective marketing messages that will affect people subconsciousness. In this regard, neuromarketing appears as a research tool for measuring subconscious reactions to marketing incentives. In this paper existing methods of neuromarketing are analyzed critically, their advantages and disadvantages are critically determined. As a result, the following groups of neuromarketing methods are distinguished: methods that measure the metabolic brain activity; methods that measure electrical brain activity; methods that measure derivative subconscious reactions. These methods make it possible to evaluate subconscious reactions, such as level of attention and emotional engagement, memory activation and other perceptual metrics. At the same time, neuromarketing has its limitations such as high costs, difficulty of searching for subjects and specialists and also negative influence of laboratory conditions during the experiments. These shortcomings should be taken into consideration combining neuromarketing with traditional research methods.